The Use of Influencer and Words of Mouth Techniques in Creating Brand Awareness @Momuung.Id - Dwita Fajardianie; Irwansyah Irwansyah (Budapest International Research and Critics University, 2022)
The development of digital technology at this time has made society as a digital society. Currently, people only need to use smart cell phones to fulfill their needs. Not only that, it also affects to the strategy in marketing a product. The use of social media that can be reached by smart mobile phones, which almost everyone has, as a promotional medium can make it easier for producers to market their products and be able to cut production costs. Among the strategies to market their products, producers often use influencers and words of mouth (WOM) techniques on Instagram. Besides being the easiest to do, nowadays people also often follow influencers who are considered capable of influencing their target market to use their products. Indonesian people also tend to share experiences in using a product, both verbally and non-verbally in their social media content. This experience is then used as a promotional event by word of mouth by the producers. On Instagram it can be seen from the testimonials written in Instagram Stories (IGS) which can be seen by their followers. The use of strategies in marketing their products is also used to increase brand awareness in the specified target market. One producer that is new and using that strategy is Mom Uung. Mom Uung is a producer of breast milk booster which currently has a target market, namely young mothers who have just had babies and actively use social media to find their needs and knowledge in terms of breastfeeding.